BASIC CURRICULUM ON CONFLICT RESOLUTION - Kurniawan, Bekti Galih; Samidi, R.; Purbasari, Verbena Ayuningsih; Marsudi, Kenlies Era Rosalina (PROGRES PENDIDIKAN, 2024)
Material for handling social conflict and preventing it needs to be provided at every level of education, including elementary schools. The hope is that through this material, the teacher's role in teaching can teach learning methods for handling conflicts within the school. This research discusses children's role in handling conflicts around them. The curriculum focuses on conflict resolution with social learning and learning objectives in implementing learning. Social issues strengthen the curriculum's conceptual framework and are used to accept students from diverse backgrounds. Apart from that, social problems are also used to understand the sources of conflict management. The method used in this research is a literature study. The discussion results in this research indicate that students were given material regarding learning from life experience, group learning methods, and material about social and political conflict. Apart from that, students are also actively involved in social education activities. Through this process, it is hoped that students can develop the ability to overcome global political issues, as well as strengthen their ability to handle conflict and improve their academic competence.